Multi-omics reveals efferocytosis-related hub genes as biomarkers for ustekinumab response in colitis - Wang, Jun-meng; Xia, Wan-yu; Liao, Yu-sha; Yuan, Jing (Frontiers in Immunology, 2025)
BackgroundDefective efferocytosis in ulcerative colitis (UC) exacerbates inflammation due to impaired clearance of apoptotic cells, yet the molecular mechanisms linking efferocytosis-related genes to therapeutic outcomes remain unclear. This study aims to investigate the role of efferocytosis in UC and the key regulatory mechanism of efferocytosis.MethodsMulti-omics integration of single-cell and bulk transcriptomic data from human UC colonic mucosa identified efferocytosis-active cellular subpopulations. Machine learning algorithms screened hub genes, followed by molecular docking to assess interactions with UST. A mouse colitis model was used to verify the inflammatory damage of UC and the key genes that play the role in efferocytosis.ResultsIn UC, the “eat me” and “digest me” signaling pathways are predominantly upregulated in myeloid cells, while the “find me” signaling cascade shows marked activation in stromal cells. Macrophages characterized by the M2 polarization demonstrate enhanced phagocytic proficiency and are instrumental in the engulfment and clearance of apoptotic cells, thereby alleviating the inflammatory cascade in UC. Six hub genes (ANXA1, PANX1, ANXA5, CD93, SERPINE1, MFGE8) were associated with UC progression and correlated with clinical response to UST. Molecular docking analysis revealed strong binding affinities between these gene-encoded proteins and UST. Transcriptomic and proteomic analyses confirmed dysregulated expression of these hub genes in the colitis model.ConclusionThis study reveals cellular heterogeneity at different stages of efferocytosis in UC, identifies efferocytosis-related genes as critical regulators of mucosal repair and predictors of UST efficacy. Findings emphasize targeting macrophage-driven efferocytosis to resolve inflammation, offering novel strategies for improving treatment outcomes.